Angiographic Evaluation of Coronary Microvascular Dysfunction in Patients with Heart Failure and Preserved Ejection Fraction. (October 2015) - Sucato, Vincenzo; Evola, Salvatore; Novo, Giuseppina; Sansone, Angela; Quagliana, Angelo; Andolina, Giuseppe; Assennato, Pasquale; Novo, Salvatore
Abstract Background The aim of this study was to evaluate myocardial perfusion and coronary blood flow through validated angiography indices to assess whether there is greater MVD in patients with microvascular angina and HFPEF compared to those who do not have. Methods Our study was performed on a population of 286 patients with stable angina that underwent coronary angiography and echocardiography. They showed epicardial coronary arteries free from stenosis. We divided the sample into two categories: patients with HFPEF and those without. We calculated indices for each patient based on angiographic images, including TFC, MBG, and TMBS. Results Our sample compared two groups: HFPEF (n = 155) and non‐HFPEF (n = 135) patients. We showed that patients with HFPEF had a longest TFC of three major coronary arteries (TFC LAD 44.7 ± 12.5; TFC RCA 26.2 ± 6.9; TFC CX 27 ± 5.9) than non‐HFPEF patients (TFC LAD 40.7 ± 11.6; TFC RCA 25 ± 6.3; TFC CX 21 ± 4.7). On the other hand, we found lower MBG on three coronary arteries (MBG LAD 2.1 ± 0.3; MBG RCA 2.1 ± 0.3; MBG CX 2.0 ± 0.32) in HFPEF than non‐HFPEF patients (MBG LAD 2.6 ± 0.5; MBG RCA 2.2 ± 0.47; MBG CX 2.3 ± 0.4). Conclusion Analysis of microcirculation through angiography indices in patients with and without HFPEF has led to assess that the HFPEF population has a greater involvement of microcirculation than patients without HFPEF.